Karakteristik Budaya Organisasi Badan Eksekutif Mahasiswa - Dian Juliarti Bantam; Nurmalinda Pangesti Haji; Alvina Laylia Faizah; Annisa Putri Sishardiyanti (Lembaga Pengembangan Kinerja Dosen, 2024)
All organizations have unique characteristics that distinguish them from other organizations. These traits form the identity of the organization. Organizational culture can help the performance of its members because it increases their motivation to give their best to take advantage of the opportunities their organization offers. The purpose of this study is to analyze the characteristics of student organizational culture in one of the BEM of a private university in Yogyakarta. The subjects in this study amounted to 3 members of the Student Executive Board. This research uses a qualitative approach with a phenomenological design. The results showed that the characteristics of Organizational Culture in BEM are respect to time, respect to people, respect to system, respect to yourself and responsibility.